2013
DOI: 10.2337/db12-1450
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Interleukin-1β Induces a Healing-Associated Wound Macrophage Phenotype and Improves Healing in Type 2 Diabetes

Abstract: Diabetes is associated with persistent inflammation and defective tissue repair responses. The hypothesis of this study was that interleukin (IL)-1β is part of a proinflammatory positive feedback loop that sustains a persistent proinflammatory wound macrophage phenotype that contributes to impaired healing in diabetes. Macrophages isolated from wounds in diabetic humans and mice exhibited a proinflammatory phenotype, including expression and secretion of IL-1β. The diabetic wound environment appears to be suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
337
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(362 citation statements)
references
References 39 publications
(51 reference statements)
22
337
1
2
Order By: Relevance
“…Macrophage dysfunction is highly relevant to the complications of obesity and diabetes, which are frequently associated with prolonged inflammation and impaired resolution/repair. The inflammasome has been linked to this disease phenotypes (31). Our data add to the mechanistic understanding of how lipids modulate macrophage biology to affect inflammation.…”
Section: Discussionmentioning
confidence: 90%
“…Macrophage dysfunction is highly relevant to the complications of obesity and diabetes, which are frequently associated with prolonged inflammation and impaired resolution/repair. The inflammasome has been linked to this disease phenotypes (31). Our data add to the mechanistic understanding of how lipids modulate macrophage biology to affect inflammation.…”
Section: Discussionmentioning
confidence: 90%
“…Studies have found that manipulating the phenotype of endogenous macrophages may be a promising therapeutic option for improving tissue repair. 28,29 In nondiabetic mice, the M1/M2 ratio peaked at day 3 and returned to baseline levels at day 10, suggesting progression to the proliferative phase of healing. In contrast, and in similarity with the proinflammatory cytokine profile, the baseline M1/M2 ratio was increased in WT diabetic mice and in NK1RKO and TAC1KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, temporal control over the administration of anti-inflammatory therapies may lead to positive outcomes. For example, Mirza et al 34 showed that the delivery of an inhibitor of the inflammatory cytokine interleukin-1-beta (IL1b) improved healing of diabetic ulcers when it was applied at three days post wounding. However, more studies are required to systematically evaluate the influence of timing of administration of proand anti-inflammatory therapeutics.…”
Section: Temporally Controlled Delivery Of Anti-inflammatory Drugsmentioning
confidence: 99%